Breast Cancers Are Immunogenic: Immunologic Analyses and a Phase II Pilot Clinical Trial Using Mutation-Reactive Autologous Lymphocytes. Issue 16 (1st June 2022) - Zacharakis, Nikolaos; Huq, Lutfi M.; Seitter, Samantha J.; Kim, Sanghyun P.; Gartner, Jared J.; Sindiri, Sivasish; Hill, Victoria K.; Li, Yong F.; Paria, Biman C.; Ray, Satyajit; Gasmi, Billel; Lee, Chyi-chia; et al.
Abstract : PURPOSE: Metastatic breast cancer (mBrCa) is most often an incurable disease with only modest responses to available immunotherapies. This study investigates the immunogenicity of somatic mutations in breast cancer and explores the therapeutic efficacy in a pilot trial of mutation-reactive tumor-infiltrating lymphocytes (TILs) in patients with metastatic disease. PATIENTS AND METHODS: Forty-two patients with mBrCa refractory to previous lines of treatment underwent surgical resection of a metastatic lesion(s), isolation of TIL cultures, identification of exomic nonsynonymous tumor mutations, and immunologic screening for neoantigen reactivity. Clinically eligible patients with appropriate reactivity were enrolled into one cohort of an ongoing phase II pilot trial of adoptive cell transfer of selected neoantigen-reactive TIL, with a short course of pembrolizumab (ClinicalTrials.gov identifier: NCT01174121 ). RESULTS: TILs were isolated and grown in culture from the resected lesions of all 42 patients with mBrCa, and a median number of 112 (range: 6-563) nonsynonymous mutations per patient were identified. Twenty-eight of 42 (67%) patients contained TIL that recognized at least one immunogenic somatic mutation (median: 3 neoantigens per patient, range: 1-11), and 13 patients demonstrated robust reactivity appropriate for adoptive transfer. Eight patients remained clinically eligible for treatment, and six patients were enrolled on a protocol of adoptive cell transfer of enriched neoantigen-specific TIL, in combination with pembrolizumab (≤ 4 doses). Objective tumor regression was noted in three patients, including one complete response (now ongoing over 5.5 years) and two partial responses (6 and 10 months). CONCLUSION: Most patients with breast cancer generated a natural immune response targeting the expressed products of their cancer mutations. Adoptive transfer of TIL is a highly personalized experimental option for patients with mBrCa shown to be capable of mediating objective responses in this pilot trial and deserves further study.